Comparing SPM12 and CAT12 segmentation pipelines: a brain tissue volume-based age and Alzheimer's disease study - Tavares, V.; Prata, D.; Ferreira, H. A. (Journal of Neuroscience Methods, 2020)
Background: Brain volumes have been used as research biomarkers both in health and in Alzheimer's disease(AD). In order to improve the comparability between studies and aid future analytical software platform choice in the research setting, here we compare two segmentation pipelines of structural brain magnetic resonance imaging(sMRI): the SPM12 toolbox, and a SPM12 add-on, the CAT12 toolbox. Methods: We segmented 1.5T and 3T T1-weighted sMRI images (from the OASIS-brain database) using both pipelines and compared them in terms of their impact on: 1)the effect of age on the total grey matter(GM) and white matter(WM), and on the hippocampi GM volumes in a healthy sample(n = 238); 2)the effect of AD diagnosis on the same volume measures; and 3)the accuracy of each volume measure detecting diagnosis (100 patients with AD and 78 age- and gender-matched healthy subjects). Results and comparison between methods: Our results demonstrated that: 1)volume estimates from SPM12 were highly correlated with the ones from CAT12, albeit absolute differences between pipelines were tissue specific; 2)the choice of pipeline modulated the effect of age on all volume measures and of diagnosis on hippocampi GM volumes computed from 3 T data; and 3)pipeline had no impact on the accuracy of any brain volume measure detecting AD diagnosis. Conclusions: Our findings indicate that other studies should take these pipeline effects on age and AD diagnosis, into account, for improved comparability in previous literature. Additionally, we encourage future studies to use CAT12 as this is a more advanced and computationally efficient brain segmentation tool.